Sodium glucose co-transporter 2 inhibitors (SGLT2i) for pediatric kidney disease: the future is near - Portalatin, Gilda M.; Hong-McAtee, Irene; Burgner, Anna M.; Gould, Edward R.; Hunley, Tracy E. (Frontiers in Pediatrics, 2025)
The sodium glucose co-transporter 2 (SGLT2) functions in the proximal tubule to reabsorb the bulk of filtered glucose. SGLT2 inhibitors have been developed to promote renal glucose excretion to improve glycemic control in diabetes. Regulatory guidance mandated adequately powered studies to detect increased cardiovascular risk from emerging hypoglycemic medications. This led to recognition of remarkable improvement in cardiovascular and kidney outcomes with SGLT2 inhibition. Moreover, cardiovascular and kidney benefits extend beyond patients with diabetes. The dramatic kidney benefits of SGLT2 inhibitors documented in CKD in adult patients underscores the need for pediatric nephrologists to familiarize themselves with SGLT2 inhibitor therapies. This review explores the currently available body of knowledge regarding the kidney protective effects of SGLT2 inhibitors in adults and mechanisms thought to contribute to improved kidney outcomes. The limited data for SGLT2i treatment in pediatric kidney disease are reviewed and highlight the need for randomized controlled trials of this drug class in pediatric kidney patients as has been done for pediatric diabetes. Dosing patterns for SGLT2 inhibitors from other pediatric settings are reviewed as well as guidance for initiating SGLT2 inhibition in young adults remaining in pediatric nephrology care.